Pathogenesis and Management of Citrin Deficiency - Hayasaka, Kiyoshi (Internal Medicine, 2024)
Citrin deficiency (CD) is a hereditary disorder caused by SLC25A13 mutations that manifests as neonatal intrahepatic cholestasis caused by CD (NICCD), failure to thrive and dyslipidemia caused by CD (FTTDCD), and adult-onset type 2 citrullinemia (CTLN2). Citrin, an aspartate-glutamate carrier primarily expressed in the liver, is a component of the malate-aspartate shuttle, which is essential for glycolysis. Citrin-deficient hepatocytes have primary defects in glycolysis and de novo lipogenesis and exhibit secondarily downregulated PPARα, leading to impaired β-oxidation. They are unable to utilize glucose and free fatty acids as energy sources, resulting in energy deficiencies. Medium-chain triglyceride (MCT) supplements are effective for treating CD by providing energy to hepatocytes, increasing lipogenesis, and activating the malate-citrate shuttle. However, patients with CD often exhibit growth impairment and irreversible brain and/or liver damage. To improve the quality of life and prevent irreversible damage, MCT supplementation with a diet containing minimal carbohydrates is recommended promptly after the diagnosis.